Implementation of a Nurse-Driven Protocol for Catheter Removal to Decrease Catheter-Associated Urinary Tract Infection Rate in a Surgical Trauma ICU. (August 2020) - Tyson, Anna F.; Campbell, Eileen F.; Spangler, Lacey R.; Ross, Samuel W.; Reinke, Caroline E.; Passaretti, Catherine L.; Sing, Ronald F.
Introduction: Early removal of urinary catheters is an effective strategy for catheter-associated urinary tract infection (CAUTI) prevention. We hypothesized that a nurse-directed catheter removal protocol would result in decreased catheter utilization and CAUTI rates in a surgical trauma intensive care unit (STICU). Methods: We performed a retrospective, cohort study following implementation of a multimodal CAUTI prevention bundle in the STICU of a large tertiary care center. Data from a 19-month historical control were compared to data from a 15-month intervention period. Pre- and postintervention indwelling catheter utilization and CAUTI rates were compared. Results: Catheter utilization decreased significantly with implementation of the nurse-driven protocol from 0.78 in the preintervention period to 0.70 in the postintervention period ( P < .05). As a result of the bundle, the CAUTI rate declined significantly, from 5.1 to 2.0 infections per 1000 catheter-days in the pre- vs postimplementation period (Incident Rate Ratio [IRR]: 0.38, 95% confidence interval: 0.21-0.65). Conclusions: Implementation of a nurse-driven protocol for early urinary catheter removal as part of a multimodal CAUTI intervention strategy can result in measurable decreases in both catheter utilization and CAUTI rates.